2023
DOI: 10.1186/s13098-023-01027-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of skeletal muscle mass and its change with diabetes occurrence: a population-based cohort study

Abstract: Background Low muscle mass likely results in reduced capacity for glucose disposal, leading to a significant but under-appreciated contribution to increasing the risk of diabetes. But few prospective studies have investigated the association between the loss of muscle mass and the occurrence of diabetes. We aimed to investigate whether short-term changes in muscle mass affect the incidence of diabetes in a Chinese population. Methods This study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Sarcopenia is associated with low glucose disposal at the skeletal muscle site [ 33 ]. Skeletal muscle is responsible for around 80% of glucose uptake during experimental conditions of euglycemic hyperinsulinemic clamp [ 34 ]. Skeletal muscle serves as a sort of buffer against hyperglycemia after a glucose load, as observed in the post-prandial phase under physiological conditions [ 35 ].…”
Section: Sarcopenia: a Determinant Of Glucose Deterioration And Poor ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia is associated with low glucose disposal at the skeletal muscle site [ 33 ]. Skeletal muscle is responsible for around 80% of glucose uptake during experimental conditions of euglycemic hyperinsulinemic clamp [ 34 ]. Skeletal muscle serves as a sort of buffer against hyperglycemia after a glucose load, as observed in the post-prandial phase under physiological conditions [ 35 ].…”
Section: Sarcopenia: a Determinant Of Glucose Deterioration And Poor ...mentioning
confidence: 99%
“…Skeletal muscle serves as a sort of buffer against hyperglycemia after a glucose load, as observed in the post-prandial phase under physiological conditions [ 35 ]. Preserving skeletal muscle mass prevents the onset of prediabetes and progression to T2D [ 34 ], as healthy insulin-sensitive skeletal muscle is essential to regulate glucose disposal. First, insulin stimulates the endothelial expression of nitric oxide synthase, nitric oxide production, and peripheral vasodilation.…”
Section: Sarcopenia: a Determinant Of Glucose Deterioration And Poor ...mentioning
confidence: 99%
“…Muscle loss and T2DM share common pathways, and both lead to impaired glucose homeostasis. Specifically, researchers have found notable commonalities in pathways associated with the onset of diabetes and SMA in adults [ 32 ]. A prospective, community-based study in older adults in China demonstrated that low baseline muscle mass and loss of muscle mass over time predicted T2DM incidence [ 32 ].…”
Section: Associations Of T2dm and Sma Lead To Adverse Clinical Outcomesmentioning
confidence: 99%
“…Specifically, researchers have found notable commonalities in pathways associated with the onset of diabetes and SMA in adults [ 32 ]. A prospective, community-based study in older adults in China demonstrated that low baseline muscle mass and loss of muscle mass over time predicted T2DM incidence [ 32 ]. By contrast, effective correction of poor glycemic control in T2DM patients (shown by a decrease in glycated hemoglobin [HbA1c] by 1% or more) was significantly associated with increased skeletal muscle mass and faster gait speed [ 33 ].…”
Section: Associations Of T2dm and Sma Lead To Adverse Clinical Outcomesmentioning
confidence: 99%
“…An association between sarcopenia (i.e., low muscle mass and strength) and ED have been shown in elderly Turkish and Korean men [33,34], and a parallel decrease in muscle strength and erectile function has been shown in men with type 2 diabetes [35]. Furthermore, muscle mass is found to be preventative of diabetes type 2 and prediabetic states [36][37][38]. In a 10-year followup study, muscle mass showed a significant inverse association with CVD incidence risk after adjusting for confounders, implicating muscle mass as cardioprotective [39].…”
Section: Introductionmentioning
confidence: 97%